Optimizing outcomes in intracranial ependymoma: a contemporary review - Pan, Zhenjiang; Bao, Jing; Wei, Shepeng (Frontiers in Oncology, 2025)
Intracranial ependymomas are glial tumors arising from the ependymal lining of the ventricular system, most commonly affecting young children (median age: 5 years), though they can occur across all age groups. Typically located in the posterior fossa, they account for fewer than 10% of pediatric central nervous system neoplasms and show a slight male predominance. Clinical symptoms vary by location, with posterior fossa tumors often causing hydrocephalus-related signs, and supratentorial lesions presenting with seizures or focal deficits. The 2021 WHO CNS5 classification integrates histologic, anatomic, and molecular features, distinguishing prognostically significant subgroups such as posterior fossa group A (PFA) and supratentorial ZFTA-fusion ependymomas. Diagnosis requires histologic confirmation, aided by MRI and cerebrospinal fluid analysis, with dissemination present in up to 10% of cases at diagnosis. Maximal safe surgical resection is the cornerstone of treatment. Children over one year with grade 2 or 3 tumors typically receive adjuvant focal radiotherapy, while chemotherapy is used to delay irradiation in infants or after subtotal resection. Disseminated disease may require craniospinal irradiation or systemic therapy. Despite multimodal treatment, prognosis remains guarded. Ten-year overall survival ranges from 50% to 75%, influenced by extent of resection, molecular subtype, and age. This review synthesizes current knowledge of ependymoma pathogenesis, classification, diagnosis, and therapy, highlighting the growing role of molecular profiling and the importance of specialized, multidisciplinary care.